Kendali Otomatis Pengisian Tangki Air 3 Tingkat Menggunakan Monitoring HMI Berbasis PLC: Simulasi Kendali Otomatis Pengisian Tangki Air 3 Tingkat Menggunakan Monitoring Hmi Berbasis Plc - Sarifudin Sarifudin; Raiadi Afgria Andika; Ryan Ananta Ismaya; M.Rafi Aryadi (INTEKNA informasi teknik dan niaga, 2023)
Air storage in people's daily lives is usually in the form of water tendons. Where the process of filling water into the tank using a manual system. It often happens that charging is useless because it uses the manual method and not a programmed system. Vain charging is the occurrence of very large waste of water. If this continues to be done, there will be a waste of ground water.Against the background of this existing problem, it is very necessary to create an automatic control system for filling the water tank. Where this automatic control system is expected to increase overall efficiency, both in terms of electricity use, air usage, and extending the life of the pump motor.The results of the tool design which is made with automatic system control on two pumps with three water tanks get very efficient results. Where control work is monitored and controlled by an HMI. The water level in the tank will be 9 conditions in the water tank whether it is empty or full. There are three pieces of information that can be obtained by the HMI, namely the water level indicator in high, medium and low conditions.